’Isa ibn ’Umayr’s Ibāḍī Theology and Donatist Christian Thought - Madelung, Wilferd (Medieval Arabic Thought: Essays in Honour of Fritz Zimmermann, 2012)
Keywords: Donatisme; Foi – Traité – 8e siècle

The authenticity of the letter of ‘Abd Allâh b. Ibâḍ to ‘Abd al-Malik - Madelung, Wilferd (Revue des mondes musulmans et de la Méditerranée, 2012)
The so-called first letter of Ibn Ibâḍ was long considered in modern scholarship as an authentic letter of ‘Abd Allâh b. Ibâḍ, the reputed founder of the Ibâḍiyya sect, to the Umayyad caliph ‘Abd al-Malik. This was questioned first by John Wilkinson and then by Michael Cook in his book on Early Muslim Theology, who proposed that the letter was written rather by Jâbir b. Zayd to the Muhallabid amîr ‘Abd al-Malik b. al-Muhallab. In his recent book on Ibadism, John Wilkinson has argued that the letter was addressed to ‘Abd al-Malik, the son of the caliph ‘Umar II, and that Jâbir b. Zayd could not have been its author. It will be argued in this paper that the letter is an authentic letter of ‘Abd Allâh b. Ibâḍ addressed to the son of ‘Umar II. Ibn Ibâḍ was not the founder of the Ibâḍiyya sect, but rather a contemporary and rival of Abû ‘Ubayda Muslim b. Abî Karîma.
ISBN: 9782853998093 Number: 132

Al-Haytham b. 'Adī on the offences of the Caliph 'Uthmān - Madelung, Wilferd (Proceedings of the 23rd Congress of L’Union Européenne des Arabisants et Islamisants : Centre and Periphery within the borders of Islam, 2012)

John C. Wilkinson, Ibâḍism: Origins and Early Development in Oman, Oxford Oriental Monographs (Oxford, U.K.: Oxford University Press, 2010). Pp. 500. $185.00 cloth. - Madelung, Wilferd (International Journal of Middle East Studies, 2012)
Keywords: Recension

Review of Early Ibāḍī Literature. Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb. Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra. (Abhandlungen für die Kunde des Morgenlandes, 75) - Prevost, Virginie (Wiener Zeitschrift für die Kunde des Morgenlandes, 2012)
Keywords: Recension

AL-SALIMI, A., and W. MADELUNG (eds.) — Early Ibadi Literature. Abu l-Mundhir Bashir b. Muhammad b. Mahbub, Kitab al-Rasf fi l-Tawhid, Kitab al-Muharaba and Sira - Custers, Martin H. (Bibliotheca Orientalis, 2012)
Keywords: Recension